The Resurrection of the Body: Authoritative Creed, Materiality, and Changes in Popular Belief in Denmark in the Eighteenth and Nineteenth Centuries. Issue 3 (16th November 2017) - Rheinheimer, Martin
Abstract : This article analyses visual and written materials which indicate some of the interesting changes that the authoritative, Christian doctrine of bodily resurrection underwent in modernity. These materials document a growing gap between the authoritative creed and people's beliefs, which cannot, I argue, be attributed solely to intellectual changes, but which was also highly reliant on changes in material living conditions and medical and hygienic progress. The article suggests that the belief in the resurrection of the body was quite firm in the general population even in the eighteenth century - the century of the Enlightenment, but that it faded towards the end of the nineteenth century due to changes in the material life conditions, such as medical progress and a decline in child mortality. My sources are gathered from the predominantly Lutheran former Duchy of Schleswig, and particularly from northern Friesland, and consist of personal letters, sermons, and visual sources such as church paintings and gravestone images. By means of selected examples, I investigate what the authoritative dogma of belief in the resurrection of the body meant to ordinary people. I trace the causes of this belief, and I discuss why it faded towards the end of the nineteenth century.